Analisis Faktor Yang Memengaruhi Pembentukkan Pola Pikir Kewirausahaan Pada Mahasiswa [Analysis of Factors that Influence the Development of Entrepreneurial Mindset in College Students] - Sembel, Jacquelinda Sandra; Valencia, Nathania (Feedforward: Journal of Human Resource, 2022)
Indonesia has the least number of entrepreneurs of only 3,10% of the population in 2020, compared to other countries, which have above 4% on average. The goal of this study is to identify the factors that influence the development of a sustainable entrepreneurial mindset in college students at a private university in Indonesia with the entrepreneurial climate at the university as the moderating variable. The study adopted a quantitative type of research with purposive sampling. The data was collected using an online survey distributed to management students at the private university. The total number of respondents recruited is 175 college students. SMART PLS 3 was used as a tool for data processing for validity, reliability, and hypothesis testing. The study revealed an interesting result: entrepreneurship curriculum and supply teaching model have a positive effect on the entrepreneurial mindset. Bahasa Indonesia Abstrak: Indonesia sebagai negara dengan jumlah populasi 271,35 juta di tahun 2020 hanya memiliki pengusaha 3,10% dari populasi, jauh lebih rendah dibandingkan negara tetangga lain yang rata-rata memiliki lebih dari 4% pengusaha dibandingkan populasinya. Tujuan dari penelitian ini adalah untuk mengidentifikasi faktor yang memengaruhi pembentukan pola pikir kewirausahaan pada mahasiswa di sebuah universitas swasta di Indonesia, dengan kondisi kewirausahaan sebagai variabel moderasi. Pengumpulan data dilakukan dengan survei secara online yang didistribusikan kepada mahasiswa program manajemen di universitas swasta tempat penelitian dilakukan. Jumlah responden yang terjaring adalah 175 mahasiswa. Data diproses dengan menggunakan SMART PLS 3 untuk melakukan tes validitas, reliabilitas dan hipotesis. Penelitian menemukan bahwa kurikulum kewirausahaan dan model pembelajaran ”˜supply’ memiliki pengaruh positif terhadap pembentukan pola pikir kewirausahaan.